Healthcare Workers’ Preparation to Provide Services for People With Disabilities - Saveljeva, Regina; Rupšienė, Liudmila; Ramanauskienė, Sada (Pedagogika, 2024)
This study aims to explore the self-reported experience in preparation to provide services for patients with disabilities among healthcare workers. Performed inferential statistics of data of 107 physicians, 218 nurses, 103 physiotherapists, and 236 social workers showed statistically significant differences between self-reported experiences in preparation to provide services for patients with disabilities. Research results will help to guide health care providers’ training and health policy and planning in Lithuania.